Modeling of Educational Technology Competency, Transformational Leadership and Self-Efficacy Towards Teachers' Professional Commitment in Multicultural Education - Faridhatul Khairiyah; Sumardi Sumardi; Yossa Istiadi (Dinasti Publisher, 2025)
This study aims to determine the effect of educational technology competence, transformational leadership and self-efficacy on teachers' professional commitment to multicultural education in public elementary schools in Grogol Petamburan District, West Jakarta. This study uses a survey method with a quantitative approach using path analysis techniques. The data for this study were obtained by questionnaire. The survey involved 173 certified teachers from 25 public elementary schools as samples using simple random sampling techniques. The results of the study showed: 1) There is a positive direct effect of educational technology competence on teachers' professional commitment to multicultural education with a path coefficient value of 0.278 and a calculated t coefficient value of 4.311, 2) There is a positive direct effect of transformational leadership on teachers' professional commitment to multicultural education with a path coefficient value of 0.306 and a calculated t coefficient value of 4.76, 3) There is a positive direct effect of self-efficacy on teachers' professional commitment to multicultural education with a path coefficient value of 0.286 and a calculated t coefficient value of 4.477. Therefore, the three calculated t coefficient values ??are greater than the t table value, so H0 is rejected and Ha is accepted, namely that educational technology competence has a direct positive effect on teachers' professional commitment to multicultural education, transformational leadership has a direct positive effect on teachers' professional commitment to multicultural education, and self-efficacy has a direct positive effect on teachers' professional commitment to multicultural education.